A two-photon ratiometric probe for detection of hNQO1 enzyme activity in human colon tissue - Cho, Myoung Ki; Lim, Chang Su; Sarkar, Avik Ranjan; Lee, Hyo Won; Choi, Hyeon Jin; Noh, Choong Kyun; Shin, Sung Jae; Kim, Hwan Myung (Sensors and Actuators, B: Chemical, 2018)
Human colonic carcinomas are one of the most common cancers in all Western countries, but there is no reliable method for quantitative and rapid analysis of colon cancer. Herein, we report an hNQO1 enzyme-selective and two-photon emission ratiometric probe (SHC) for quantitative analysis of hNQO1 activity in human colon tissue. This probe shows a blue-to-yellow emission color change in response to hNQO1, high sensitivity and selectivity for hNQO1 over other bio-metabolites, and two-photon microscopy (TPM) imaging capability, thereby allowing precise monitoring of the activity of hNQO1 in situ. Ratiometric TPM imaging with SHC in human colon tissues revealed that hNQO1 activities gradually increased during cancer progression from normal to adenoma, and to adenocarcinoma colon tissues. These findings demonstrated that SHC labeling can detect the differential activities of hNQO1 in the distinct stages of colon neoplasm. Thus, this approach, enzyme-selective TP probe labeling, will likely provide a reliable and fast method for precise diagnosis of colon cancer.
Keywords: Cancer progression; Colon cancer; Differential activity; Fluorescent probes; Imaging capabilities; Ratiometric imaging; Two photon microscopy; Two-photon emission; Colon cancer; Enzyme activity; Fluorescent probe; Ratiometric imaging; Two-photon microscopy